Perancangan User Experience Aplikasi Penyewaan Perlengkapan dan Mainan Anak berbasis Mobile di Kabupaten Jombang menggunakan Metode Human-Centered Design - Fikri Alfi Hidayatulloh; Agi Putra Kharisma; Mahardeka Tri Ananta (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
Rental services for children's equipment and toys are starting to be in great demand by the community in Jombang Regency, according to observations in Jombang Regency itself, there are more than 10 UMKM that provide rental services for children's equipment and toys. The children's equipment and toys rental application (JoJo) is an application designed for the Jombang community to make it easier for the community to use equipment and children's toy rental services in Jombang Regency. This study aims to create an application design that is good in terms of user experience and usability for its users. The method chosen to design user experience in this research is Human-Centered Design (HCD) which focuses on the human perspective in each process consisting of context analysis and user needs, creating design solutions, and design evaluations. The design evaluation obtained using usability testing is 100% for the effectiveness aspect, 0.0592 goals/second for the efficiency aspect, and on the aspect of user satisfaction, the score is 91.75 with grade A. Then the results of the User Experience Questionnaire (UEQ) are in the excellent category on the attractiveness, efficiency, dependability, stimulation, and novelty aspects and the good category on the perspicuity aspect. From the results of the design evaluation, it shows that the solution design has a good level of usability and also has a positive user experience for users because it gets a value that is more than the average in every aspect.